2023
DOI: 10.1055/a-2081-1560
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation for Children with Cerebral Palsy: A Meta-analysis for Randomized Controlled Trials

Abstract: Background: Different types of electrical stimulation (ES) showed diverse effects on children with cerebral palsy (CP). Previous studies reported inconsistent results for effect of ES on children with CP. The present study aimed to make a meta-analysis to summarize these diverse results. Methods: We searched for studies exploring effect of ES on children with CP in databases (Pubmed and Web of Science) from their inception until December, 2022. Standard mean differences (SMDs) and 95% confidence intervals (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In clinical practice, the treatment of children with a crouching gait often requires the assistance of ankle-foot orthoses and gait rehabilitation robots. Ankle-foot orthoses are an effective physiotherapy intervention to improve gait and studies have shown that wearing ankle-foot orthoses can reduce pathological reflex patterns and energy expenditure for walking, significantly improving motor function in children with cerebral palsy [15]. The overall mechanism of action of orthoses is the correction of lower limb force lines.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the treatment of children with a crouching gait often requires the assistance of ankle-foot orthoses and gait rehabilitation robots. Ankle-foot orthoses are an effective physiotherapy intervention to improve gait and studies have shown that wearing ankle-foot orthoses can reduce pathological reflex patterns and energy expenditure for walking, significantly improving motor function in children with cerebral palsy [15]. The overall mechanism of action of orthoses is the correction of lower limb force lines.…”
Section: Discussionmentioning
confidence: 99%